THE PRACTICAL VALUE OFOXIDATIVE STRESS MARKERS IN PATIENTS WITH PYELONEPHRITIS - L. Korol; N. Stepanova; L. Migal (Ukrainian Journal of Nephrology and Dialysis, 2016)
The work is dedicated to the practical application of oxidative stress markers and the possibility of using them for monitoring and optimize the treatment o fpatients with pyelonephritis